Service 4.0: Technology-enabled customer-centric supply chains - Kang, Parminder Singh; Wang, Xiaojia; Son, Joong Y.; Jat, Mohsin (My University, 2024)
This book presents a systematic framework for Service 4.0, including service digitization, digitalization, and digital transformation, which is an integral part of Supply Chain 4.0 in coping with complex, dynamic, and interdependent systems. It provides a comprehensive state-of-the-art review of digital technologies to support Service 4.0 and Supply Chain 4.0, and discusses important pillars of customer-centric supply chain models. It then explains the role of big data in customer-centric service-based supply chains and links the different types of data needed to promote end-to-end transparency and value co-creation activities to promote these key pillars. Moreover, the book introduces practical models to support analytics for customer-centric supply chains and sheds light on how the industry practically uses existing models to promote service co-creation. A chapter of a case study on women's clothing e-commerce reviews and demonstrates how various data visualization and text mining methods can be used to uncover meaningful insights within the review data. The book is intended to help students and researchers quickly navigate through various technologies and future research directions in the areas of Service 4.0 and Supply Chain 4.0. It is also a valuable read for practitioners in this field.
Keywords: Service 4.0; Supply Chain 4.0; customer-centric supply chains; analytics models; service operations management; service inventory management; inventory analytics; innovation and technology management; supply chain management